CTLA-4 directly inhibits osteoclast formation. Issue 11 (18th January 2008) - Axmann, R; Herman, S; Zaiss, M; Franz, S; Polzer, K; Zwerina, J; Herrmann, M; Smolen, J; Schett, G
Abstract : CTLA-4 is a regulator of co-stimulation and inhibits the activation of T cells through interfering with the interaction of CD80/86 on antigen-presenting cells with CD28 on T cells. CTLA-4 binds to the surface of antigen-presenting cells, such as dendritic cells and monocytes through CD80/86. Monocytes can differentiate in osteoclasts, the primary bone resorbing cells. Herein, we investigated whether the binding of CTLA-4 affects the differentiation of monocytes into osteoclasts in vitro and vivo. We show that CTLA-4 dose-dependently inhibits RANKL- as well as tumour necrosis factor (TNF)-mediated osteoclastogenesis in vitro without the presence of T cells. Furthermore, CTLA-4 was effective in inhibiting TNF-induced osteoclast formation in a non-T cell dependent TNF-induced model of arthritis as well as the formation of inflammatory bone erosion in vivo. These data suggest that CTLA-4 is an anti-osteoclastogenic molecule that directly binds osteoclast precursor cells and inhibits their differentiation. These findings are an attractive explanation for the anti-erosive effect of abatacept, a CTLA-4 immunoglobulin fusion protein used for the treatment of rheumatoid arthritis.